Uruguay : 2006 Article IV Consultation, Fourth Review Under the Stand-By Arrangement and Request for Waiver of Nonobservance and Modification of Performance Criteria; Staff Report; Staff Statement; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report, 2006)
With the recovery from the 2002 crisis well advanced, discussions focused on policies to reduce remaining vulnerabilities and sustain growth. Sensitivity analysis suggests that the economy, while having become more resilient in recent years, is still vulnerable. The authorities agreed to continue increasing buffers and strengthening Uruguay's underlying performance, noting that under current strong policies and expected continued favorable external conditions, vulnerabilities should decline considerably with time. The estimates of sustainable expenditure paths for Russia are assessed. This study concludes by summarizing the policy implications of the analysis.